A Tunable Capacitor Based on MEMS Technology for RF Applications - Teymoori, M. M.; Ahangarkolaei, J. M. (Engineering, Technology & Applied Science Research, 2016)
A tunable capacitor based on MEMS technology is presented in this paper. The proposed structure consists of two fixed-fixed parallel movable plates with 4 supports. Movability of two plates makes it possible to actuate the plates with a small voltage. When the actuation is applied, two plates move together and their distance is decreased, hence the capacitance is increased and tuning is achieved. The structure is simulated through the finite element method using COMSOL and ANSOFT HFSS software. Simulation results show that the actuation voltage required to access the 59% tuning, is 7 V. The effective area of the designed tunable capacitor is 200 x 200 µm2 with a thickness of 2 µm. The quality factor is 91 at 11 GHz which is sufficient for various RF communication applications such as filters, transceivers and so on. The low stress induced on the plates and low actuation voltage, are the main advantages of the design.